2020
DOI: 10.3390/jmse8100791
|View full text |Cite
|
Sign up to set email alerts
|

ISO 15016:2015-Based Method for Estimating the Fuel Oil Consumption of a Ship

Abstract: Recently, interest in the design and construction of smart ships has been widely increasing. Optimal route planning is a widely studied essential aspect of smart ship technology. Planning an optimal route requires an accurate estimation of the fuel oil consumption of a ship. Various studies have suggested methods for theoretically estimating the fuel oil consumption. However, the calculation methodology and accuracy are different for each method. In addition, in commercial software, a statistical model based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The datadriven methodologies can be used to calculate the propulsion power and fuel consumption for a ship cruise. Support vector regression (SVR) was used in a study in this area to predict propulsion power more accurately than conventional methods [5,41]. Another study indicated that machine learning approaches outperform the ANN method in specific cases for predicting shaft power onboard ships using AIS data and weather data [42].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The datadriven methodologies can be used to calculate the propulsion power and fuel consumption for a ship cruise. Support vector regression (SVR) was used in a study in this area to predict propulsion power more accurately than conventional methods [5,41]. Another study indicated that machine learning approaches outperform the ANN method in specific cases for predicting shaft power onboard ships using AIS data and weather data [42].…”
Section: Methodsmentioning
confidence: 99%
“…Various rules and regulations were enacted by the International Maritime Organization (IMO) to limit emissions in the shipping industry [3,4]. Therefore, several indices such as the Energy Efficiency Design Index (EEDI), Ship Energy Efficiency Management Plan (SEEMP), and Energy Efficiency Operational Indicator (EEOI) have been proposed to determine and enhance the energy efficiency level of the global fleet of marine vessels [5]. In terms of shipping companies, it can be claimed that energy efficiency begins at the design stage [6] and that ship energy efficiency may be boosted through operational ways in addition to numerous design approaches [7][8][9][10].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…The simplest method is to estimate fuel consumption using total engine power and specific fuel consumption. Kim et al [17] proposed a method for estimating fuel consumption based on theoretical resistance calculations, which applied methods [18,19] and the ship's propulsion parameters, among others. Bialystocki and Konovessis [20] proposed an operational approach to estimate fuel consumption and speed based on the main influencing factors, such as ship draught and displacement, wind speed and direction, hull and propeller roughness.…”
Section: The Estimation Of Fuel Consumptionmentioning
confidence: 99%
“…where C a is the air resistance coefficient as a function of γ R ; the relative angle between wind direction and the ship's motion, ρ a is air density, A is the ship surface area opposed to the wind, v is the ship's speed over ground, and w R is the relative wind speed. C a was fitted for this study according to laden conditions of a container ship described in [36], which was then used to model the air resistance coefficients dependency on wind direction for all of the studied ships. This was deemed reasonable, as the shape of the function does not differ substantially across ship types, and C a functions were not publicly available for the studied ships specifically.…”
Section: Ship Performance Modelmentioning
confidence: 99%